2002
DOI: 10.1046/j.1528-1157.2002.29201.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Double‐blind Parallel‐group Study Comparing Cognitive Effects of a Low‐dose Lamotrigine with Valproate and Placebo in Healthy Volunteers

Abstract: Summary:Purpose: This study aimed at investigating the cognitive and mood effects of lamotrigine (LTG) versus valproate (VPA) and placebo (PBO).Methods: By studying the effects in healthy volunteers, it is possible to separate the genuine effects of LTG from the cognitive improvements, caused by better seizure control. The study used a pretest-posttest comparison of 50 mg LTG, 900 mg VPA, or PBO in a double-blind single-dummy parallelgroup design with 30 healthy volunteers. Study duration was 12 days (with a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
1
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 24 publications
(26 reference statements)
4
39
1
5
Order By: Relevance
“…In patients with seizures, lamotrigine appears to have a more benign effect on cognition than some other antiseizure medications (Pressler et al, 2006). In healthy controls (Aldenkamp et al, 2002) and in animal models (Shannon and Love, 2004) lamotrigine appears to be associated with no significant changes in cognitive performance. In patients with bipolar disorder, both improvement (Daban et al, 2006) and worsening of cognitive performance (Osuji et al, 2007, in press) have been reported with lamotrigine.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with seizures, lamotrigine appears to have a more benign effect on cognition than some other antiseizure medications (Pressler et al, 2006). In healthy controls (Aldenkamp et al, 2002) and in animal models (Shannon and Love, 2004) lamotrigine appears to be associated with no significant changes in cognitive performance. In patients with bipolar disorder, both improvement (Daban et al, 2006) and worsening of cognitive performance (Osuji et al, 2007, in press) have been reported with lamotrigine.…”
Section: Discussionmentioning
confidence: 99%
“…The superiority of lamotrigine over older AEDs has been demonstrated in multiple healthy volunteer studies (A. P. Aldenkamp et al 2002;Cohen et al 1985;Hamilton et al 1993).…”
Section: Lamotrigine (Lamictal)mentioning
confidence: 96%
“…An open-label study in patients diagnosed with Alzheimer's disease showed some treatment improvement in depressed mood, word recognition, and naming with lamotrigine treatment (Tekin et al 1998), and lamotrigine may have a beneficial effect on cognition in patients with epilepsy (Aldenkamp and Baker 2001). Furthermore, healthy volunteers on low doses of lamotrigine showed improvement on measures of cognitive activation and alertness (Aldenkamp et al 2002).…”
Section: Interactions With Antipsychotic Drugsmentioning
confidence: 99%